2023
DOI: 10.1186/s12889-022-14932-w
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of COVID-19 pandemic on low back pain: data from the PAMPA Cohort, Brazil

Abstract: Background To evaluate the short-term impact of COVID-19 pandemic on low back pain (LBP) outcomes in southern Brazil. Methods Data from the PAMPA Cohort were analyzed. Adults were recruited between June and July 2020 in the Rio Grande do Sul state using online-based strategies. Participants responded a self-reported, online questionnaire on LBP with two timepoints: before (retrospectively) and during COVID-19 pandemic. We assessed LBP experience, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In Bangladesh, Ali M et al found that Overall, 20% of participants reported LBP; however, the prevalence of LBP was significantly higher among patients with post-acute COVID-19 compared with their counterparts (24.4% vs 15.7%, P=0.001) [ 20 ]. On the other hand, Caputo EL et al in Brazil revealed that the prevalence of LBP did not change significantly from before (74.7%) to the first months of the pandemic (74.2%) but increased pain levels and a higher likelihood for activity limitation due to LBP were observed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, Ali M et al found that Overall, 20% of participants reported LBP; however, the prevalence of LBP was significantly higher among patients with post-acute COVID-19 compared with their counterparts (24.4% vs 15.7%, P=0.001) [ 20 ]. On the other hand, Caputo EL et al in Brazil revealed that the prevalence of LBP did not change significantly from before (74.7%) to the first months of the pandemic (74.2%) but increased pain levels and a higher likelihood for activity limitation due to LBP were observed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A numeric pain rating scale was used to assess pain intensity, ranging from 0 (no pain) to 10 (worse pain). Activity limitation was assessed by asking participants if their pain was strong enough to limit or change their daily activities for at least one day [5].…”
Section: Lbp Intensity Activity Limitation and Care Seekingmentioning
confidence: 99%
“…LBP incidence may be directly related to inappropriate postures while working, extended periods of sitting, physical inactivity, and high stress and anxiety levels [1,2]. During COVID-19 the pandemic restrictions, a decrease in physical activity levels and an increase in anxiety and depression was observed, being strongly related to LBP outcomes in the initial months of the restrictions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing prepandemic and postpandemic scores point toward the presence of subgroups, with some individuals showing improved pain scores, whereas others showing pain deterioration. 1,10 Similarly, unchanged pain, emotional distress, and opioid misuse patterns were found over a 1-year period among adults with chronic pain, 27 whereas improvements in pain intensity and depression scores were found in patients with chronic pain when studied over the course of the first 2 years of the pandemic. 47 Such understanding of individuals' long-term pain and psychological distress trajectories taking into account prepandemic status, however, is lacking.…”
Section: Introductionmentioning
confidence: 97%